Has the Landscape of Immunotherapy for Prostate Cancer Changed? A Systematic Review and Post Hoc Analysis. Issue 2 (April 2023) - Ashraf, Muhammad Usman; Farwa, Ume; Siddiqa, Maryam; Sarfraz, Azza; Azeem, Nishwa; Sarfraz, Zouina
Prostate cancer (PCa) is the second leading cause of cancer-causing death in the United States. As the most common malignancy in men, it is pertinent to explore whether novel immunotherapies may improve the quality of life and overall survival (OS) of patient populations. This systematic review and post hoc analysis curates a patient-by-patient pool of evidence adhering to PRISMA Statement 2020 guidelines. In total, 24 patients were analyzed for treatment history and associated variables including prostate-specific antigen (PSA) levels at diagnosis and post-treatment, Gleason score, secondary tumor locations, success/failure of therapy, and post-immunotherapy outcomes including OS. In total, 10 types of immunotherapies were identified with Pembrolizumab (among 8 patients) followed by IMM-101 (among 6 patients) being the most commonly administered. The mean OS for all patients was 27.8 months (24 patients) with the relatively highest mean OS reported with IMM-101 (56 months) followed by tumor-infiltrating lymphocytes (30 months). This research article provides critical insights into the evolving landscape of immunotherapies being tested for PCa and addresses gaps in oncological research to advance the understanding of PCa.